PENELITIAN UNTUK PENGEMBANGAN SISTEM ISYARAT DINI DAN INTERVENSI - Abas. B. Jahari; Atmadi Purnomo; Djumadias Abunain; Iman Sumarno; R.M. Brooks; Sri Prihatini; Untung Supariadi; David F. Williamson; Mashari Sudjono (Persagi, 1984)
-